Anthropometry in Children with Transfusion-Dependent Beta-Thalassemia Major - Nisa, Noor Un; Ikram, Farooq; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the abnormal anthropometric findings among children diagnosed with and managed for transfusiondependent beta-thalassemia major.Study Design: Cross-sectional study.Place and Duration of Study: Department of Paediatric Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2019 to Aug 2020.Methodology: This study involved 310 children of both genders aged 2 to 18 years presenting with beta-thalassemia Major receiving multiple blood transfusions. Anthropometric findings, including height and weight for age, were measured and plotted via World Health Organization-2007 growth charts in all the study participants. Relevant socio-demographic variables, including serum ferritin, were correlated with abnormal anthropometric findings among these children.Results: The mean age of the patients was 8.87±7.42 years. 170(54.8%) male and 140(45.2%) female patients were in the study group. Most of the children [218 (70.3%)] had any abnormal an-thropometric findings, either weight or height for age, while 92 (29.7%) had no anthropometric abnormality. Majority of the patients [198 (63.8%)] patients had stunted growth, while 170 (54.8%) were underweight. Longer duration of transfusion and raised serum ferritin levels had a statistically significant correlation with any anthropometric abnormality among the beta-thalassemia major patients (p-value